WHO is in and WHO is out of the mouth, salivary glands, and jaws sections of the 4th edition of the WHO classification of head and neck tumours. Issue 2 (February 2018) - Kennedy, R.A.
Abstract: This review of changes to the 4th edition of the WHO classification of head and neck tumours focuses on their impact on the surgical care of diseases that affect the salivary glands, jaws, and oral cavity. Updates to the chapter on the salivary glands include the addition of secretory carcinoma and sclerosing polycystic adenosis. The odontogenic cysts are back, and the odontogenic keratocyst is listed among them, as it has now lost its brief and confusing designation as a neoplasm. The newly-defined sclerosing odontogenic carcinoma and primordial odontogenic tumour have been added. Oropharyngeal tumours have been separated from those of the oral cavity, which reflects the importance of HPV in carcinoma of the tonsils. The problems of grading oral epithelial dysplasia persist.